Pelatihan Aplikasi XRecorder untuk Media Pembelajaran Daring bagi Guru SD - Ratri Rahayu; Himmatul Ulya (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2022)
The outbreak of the Covid-19 virus impacted changing learning activities from face-to-face to online. This transition raises many obstacles for teachers, especially the use of technology. SDN 2 Margoyoso teachers have difficulty making video explanations of subject matter. The teacher only sends text messages in the form of instructions for doing assignments without sending learning videos. This makes students bored and unable to understand the lesson's content well. This service activity aims to provide knowledge to SDN 2 Margoyoso teachers about the use of the XRecorder application for online learning media. This service activity was conducted at SDN 2 Margoyoso with one school principal and 13 teachers as participants. The action was held on February 15 and 18, 2021. The method used in this service was to provide interactive training and training. Furthermore, there is a two-way interaction in the training process to provide opportunities for teachers at SDN 2 Margoyoso as training participants to contribute their ideas, opinions, thoughts, and experiences. The training is carried out in several stages, including planning, implementation, follow-up, and evaluation. Training service activities were able to improve teacher skills in online learning innovation. This was manifested by teachers at SDN 2 Margoyoso being able to simulate and practice using the XRecorder application in online learning videos.